The Impact of Emotional Intelligence on the Well-Being of Students from Public Sector Medical College; Mediating Role of Perceived Stress : Impact of Emotional Intelligence on the Well-Being of Students - Latif, Saima; Dickson, Kamal; Hanif, Sameen (Pakistan Journal of Health Sciences, 2024)
Healthcare sector play key role for the wellbeing of overall society. This tiring job of providing efficient and effective healthcare services has severe consequences on the health and personal life of healthcare workers. Previously, studies have emphasized on the wellbeing of the healthcare workers, however, students of medical profession were ignored even they go through the burden while learning the theoretical courses and practical exposure in hospitals. The pressure of theoretical classes and rotational trainings in the hospitals causes stress and ultimately influence their wellbeing. Objective: To investigates the relationship between emotional intelligence and psychological well-being (Life satisfaction and Happiness) of the medical students through mediation of perceived stress. Methods: Self-administered questionnaire was distributed to 350 MBBS and BSN students of Allama Iqbal Medical College through convenient sampling. Consent of the respondents, privacy and other ethical requirements were fulfilled. Finally, 201 (MBBS; 103, BSN; 98) medical students from Allama Iqbal Medical College responded the questionnaire. SPSS version 21.0 was used to analyze the data. Results: The results revealed that there exists positive and significant relationship between emotional intelligence and medical student’s well-being (Life satisfaction and Happiness). Further, perceived stress significantly mediates the relationship of emotional intelligence and wellbeing. Conclusions: This study results found that emotional intelligence and medical student’s well-being (Life satisfaction and Happiness) have positive and significant association.